2012
DOI: 10.4236/ajac.2012.33027
|View full text |Cite
|
Sign up to set email alerts
|

Donnan Electric Potential Dependence of Intraparticle Diffusion of Malachite Green in Single Cation Exchange Resin Particles: A Laser Trapping-Microspectroscopy Study

Abstract: A laser trapping-microspectroscopy technique combined with excitation energy transfer from a fluorescent cationic dye (Rhodamine B, RB + ) to a non-fluorescent cationic dye (Malachite Green, MG + ) was employed to study pH effects on the diffusion coefficients of MG + (D(MG + )) in single cation-exchange resin microparticles with the diameters of 16 μm. When RB + -pre-adsorbed resin particles were soaked in an aqueous MG + solution, the RB + fluorescence was quenched gradually with the soaking time. The time c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our next target was to resolve the other anomaly between pH 7 and 9, where in spite of k OM remaining nearly constant, k IM increased exponentially. Though this effect can be misinterpreted easily as the effect of MG + to MGOH conversion having p K a value 6.9, we already showed that, in the range pH 7–9, only less than 10% conversion takes place during the SHG experiment (Table S1). Therefore, any changes in membrane permeability due to formation of neutral MGOH will hardly contribute to the increase of k IM of MG + .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Our next target was to resolve the other anomaly between pH 7 and 9, where in spite of k OM remaining nearly constant, k IM increased exponentially. Though this effect can be misinterpreted easily as the effect of MG + to MGOH conversion having p K a value 6.9, we already showed that, in the range pH 7–9, only less than 10% conversion takes place during the SHG experiment (Table S1). Therefore, any changes in membrane permeability due to formation of neutral MGOH will hardly contribute to the increase of k IM of MG + .…”
Section: Resultsmentioning
confidence: 93%
“…This factor is very important for our investigation, since different charge states may have different extent of adsorptions on cell membrane surfaces and therefore may yield different amplitude of SHG signals. Our probe molecule MG exists as MGH 2+ , MG + , and MGOH between pH 3 and 9 . Concentrations of these charge states ideally should be calculable from the p K a values of MG (p K a 1 ≈ 1 and p K a 2 = 6.9, Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…At pH values greater than 6.9 (Cuong et al 2012) malachite green is chemically reduced to its carbinol form which can undergo a 2e -oxidation to give malachite green and a hydroxyl ion. The carbinol form is more non-polar in nature and hence would explain the reactant adsorptive behaviour seen in our investigation.…”
Section: Resultsmentioning
confidence: 99%